2021
DOI: 10.1088/1755-1315/713/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and sensory characteristics of brownies from composite flour (modified breadfruit, purple sweet potato, saga seeds, and mocaf)

Abstract: Breadfruit is a plant that has potential as a national food security reserve because breadfruit is able to produce throughout the year, breadfruit is also a vegetable food ingredient that contains a lot of carbohydrates. Purple sweet potato can improve the taste of food processing products, because of its distinctive purple color, and high nutritional content. Saga seeds are high protein-producing plants concurrently increasing the nutritional value of food, and mocaf is the result of cassava fermentation by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…r Brownie preparation The preparation method for steamed brownies followed that described by Lubis et al [2021] with a slight modification. First, the dry ingredients, such as flour blend or wheat flour (WF), powdered sugar, cocoa powder, baking powder, and salt, were mixed until homogeneous in a container (mixture 1).…”
Section: Materials and Methods R Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…r Brownie preparation The preparation method for steamed brownies followed that described by Lubis et al [2021] with a slight modification. First, the dry ingredients, such as flour blend or wheat flour (WF), powdered sugar, cocoa powder, baking powder, and salt, were mixed until homogeneous in a container (mixture 1).…”
Section: Materials and Methods R Materialsmentioning
confidence: 99%
“…Previous studies have reported that steamed brownies from 100% modified cassava flour [Lubis et al, 2021] and 100% pumpkin flour [Subaktilah et al, 2021] had lower protein contents. Furthermore, Lubis et al [2021] reported that steamed brownies with a flour blend from breadfruit flour, purple sweet potato flour, modified cassava flour, and saga seed flour with a ratio of 35:45:5:15 (w/w/w/w), had weaker aroma and good volume expansion compared to wheat flour steamed brownies. Meanwhile, steamed brownies with 100% suweg flour [Bela Monica & Setyaningrum, 2022] and 100% purple sweet potato flour [Lubis et al, 2021] produced a dark color and dense texture.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Tanpa adanya pengawetan, gula aren akan rusak apabila dibiarkan selama kurang lebih 2,5 jam. Beberapa komoditi pertanian harus langsung dikonsumsi atau diolah dahulu karena dihasilkan dari bahan mentah dan mudah rusak (Lubis et al, 2013). Pengawet sintesis ataupun alami dapat menghambat terjadinya kerusakan pada nira.…”
unclassified